2012
DOI: 10.1353/hpu.2012.0179
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of Impact of Medical-Legal Partnership Services on Patients’ Perceived Stress and Wellbeing

Abstract: Services in patient-centered medical homes to address unmet legal needs have the potential to reduce perceived stress and improve overall wellbeing. Additional studies concerning MLPs and patient outcomes are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 24 publications
1
53
0
1
Order By: Relevance
“…Previous empirical research on the MLP model is limited but existing studies demonstrate encouraging results in the pairing of doctors and lawyers for patient health (Pettignano et al, 2013; Beeson et al, 2013; Ryan et al, 2012; Beck et al, 2012; Sandel et al, 2010; Hernández, 2010; Cohen et al, 2010; Weintraub et al, 2010; Zuckerman, 2012; Zuckerman et al, 2008, Teufel et al, 2008; Zuckerman et al, 2004). Weintruab and colleagues reported improved child health outcomes and greater utilization of food and income supports on the part of parents.…”
mentioning
confidence: 99%
“…Previous empirical research on the MLP model is limited but existing studies demonstrate encouraging results in the pairing of doctors and lawyers for patient health (Pettignano et al, 2013; Beeson et al, 2013; Ryan et al, 2012; Beck et al, 2012; Sandel et al, 2010; Hernández, 2010; Cohen et al, 2010; Weintraub et al, 2010; Zuckerman, 2012; Zuckerman et al, 2008, Teufel et al, 2008; Zuckerman et al, 2004). Weintruab and colleagues reported improved child health outcomes and greater utilization of food and income supports on the part of parents.…”
mentioning
confidence: 99%
“…3,4 The inclusion of an MLP in the care team has also demonstrated decreased parental stress. 5 When our MLP was formed, we completed a needs assessment to identify the issues most important to our patients and providers and aligned these legal needs with the attorneys' expertise. Our MLP's primary focus has included housing conditions and evictions, public benefits including health insurance, educational issues, intimate partner violence, and more recently, immigration.…”
Section: Launched In 2008 Our Mlp a Collaboration Between Legal Aidmentioning
confidence: 99%
“…MLPs address the social determinants of health by meeting the civil legal needs of patients . The inclusion of an MLP in the care team has also demonstrated decreased parental stress . When our MLP was formed, we completed a needs assessment to identify the issues most important to our patients and providers and aligned these legal needs with the attorneys’ expertise.…”
mentioning
confidence: 99%
“…75 Studies indicate that MLPs can reduce subjective stress and improve self-reported well-being, legal problem-solving skills and sense of empowerment, and health care utilization and self-reported health and well-being. [78][79][80] MLPs have also been successful at leading community-level change. 81 Other studies have addressed program sustainability, demonstrating the ability to provide financial benefit to the clinical setting by resolving improperly denied insurance claims.…”
Section: Mlpsmentioning
confidence: 99%